Axial compression stability of thin double-steel-plate and concrete composite shear wall. (December 2021) - Chen, Zhihua; Zi, Zhenyu; Zhou, Ting; Wu, Yapeng
Abstract: Double-steel-plate and concrete composite shear walls have the characteristics of high structural strength, good seismic performance, and convenient construction. The thickness of the double-steel-plate and concrete composite shear wall, used in structural systems composed of special-shaped columns with concrete-filled square steel tubes, is only approximately 130 mm, and the height-to-thickness and width-to-thickness ratios are large in the plane of the wall. However, the thickness of the double-steel-plate and concrete composite shear walls that have been studied is relatively large, and their aspect ratio and width are relatively small. The bearing capacity, stability, and coordination of the steel plate and concrete under axial pressure are not clear. Therefore, this study conducts an experimental research by changing the height and connection type of the wall, and five thin double-steel-concrete composite shear wall test pieces were designed and tested under axial pressure loading. At the same time, the experimental results are compared with the results of a finite element analysis. The result shows that the axial compression ratio limit of the thin double-steel-plate composite shear wall is 0.45. When the wall height is relatively small, the damage mode is steel plate bulge and axial crushing. When the height-to-thickness ratio is greater than 12, the failure mode is steel plate bulge and overall instability. The wall can be used in actual projects within the axial compression ratio. The axial rigidity, ultimate bearing capacity, and material strength utilization efficiency of the wall decrease significantly with the increase in height. The connection method has no obvious effect on the stiffness of the section. The test piece with a relatively large height and thickness has an out-of-plane displacement, and the actual axial stiffness is lower than the theoretical calculated stiffness. Compared with the uniaxial compressive strength of concrete, the improvement in concrete compressive strength is limited. Welded stiffeners on the surface of the steel plate can limit the local buckling of the steel plate. The calculation method of the overall stability coefficient of the wall under the action of axial pressure derived from the comprehensive test and finite element simulation in this study is reliable.